2016
DOI: 10.1177/0748233716659840
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the oxidative stress condition for occupational exposure to methyl methacrylate

Abstract: The purpose of this study is the evaluation of possible toxicological effects on dental personnel, who are exposed to the production materials of prostheses during their entire working life. In this study, the level of methyl methacrylate (MMA) in ambient air was measured as an indicator of external exposure on the personnel. In order to evaluate the possible toxic effects of oxidative stress, which is thought to play an important role in the formation process of many diseases such as cancer, blood samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Furthermore, there were no differences in the expression levels of IL-8 in the control and treatment groups. However, these results cannot be extrapolated to those of chronic exposure [15]. At low levels of MMA exposure, an adaptive response can occur [16].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there were no differences in the expression levels of IL-8 in the control and treatment groups. However, these results cannot be extrapolated to those of chronic exposure [15]. At low levels of MMA exposure, an adaptive response can occur [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the genotoxic potential of dental laboratory material used by dental technicians . A survey by Burgaz et al compared dental technicians exposed to metal alloys to a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the genotoxic potential of dental laboratory material used by dental technicians. 2,7,24 A survey by Burgaz et al 7 compared dental technicians exposed to metal alloys to a control group. Their data revealed that in vivo exposure to chromium, nickel, and cobalt metals is evident and contributes to the genotoxic damage in lymphocytes and exfoliated nasal cells; however, which compound(s) are responsible for the genotoxic damage could not be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained from murine macrophages in vitro revealed that BISGMA exhibited genotoxicity in a dose-related fashion as a result of increasing numbers of DNA strand breaks and micronuclei formation (23). When people were occupationally exposed to methyl methacrylate, superoxide dismutase activity, malondealdehyde, and glutathione levels were significantly higher in blood samples of dental technicians when compared to matched controls (24). Analogous products, such as 2,2-bis [4-(acryloxypropoxy)phenyl]propane also increased micronuclei frequency in human gingival fibroblasts in vitro (25).…”
Section: Dental Restorative Materials and Related Compoundsmentioning
confidence: 99%